Persepsi Siswa dan Guru terhadap Pengembangan Multimedia Berbasis Aplikasi Android - Abdul Haris Faisal; Zuriyati Zuriyati; Eva Leiliyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine students 'and teachers' perceptions of the results of developing android-based multimedia applications on poetry material for high school students in class X. This study uses descriptive qualitative methods. The results of this study indicate that students' perceptions of the development of application-based learning multimedia on poetry material obtained an average score of 3.82 with a decent category. The results of the assessment of Indonesian language teacher scores 4.23 in the very feasible category. Conclusion, the use of andriod-based multimedia applications is appropriate for use in poetry learning activities in high school. Keywords: Perception, Multimedia, Android-based